PATHOPHYSIOLOGICAL CHANGES IN LIVER TISSUES OF HYPERCALORIE DIET-INDUCED OBESE RATS - Ambadasu, Bharatha; S, Ramadevi; Aa, Naikawadi; M, Naveen Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Hypercalorie diet intake has been associated with many long-term complications including metabolic syndrome, cardiovascular diseases, and nonalcoholic fatty liver disease. Methods: A total of 12 Wistar rats either sex were used in this study. These animals were randomly divided into two groups as control and obese rats. Group 1 consists of six rats weighing 150-200 g and fed with normal pellet chow. Another six rats were fed hypercalorie/cafeteria diet to induce obesity and included in the study after 19 weeks of age. All animals were sacrificed; liver tissues were collected, weighed and sent for the histopathological examination. Results: Weight of liver tissues of was significantly more in obese rats than the control rats. Histopathological examination shows an excessive fat deposition and sinusoidal congestion in the liver tissues of obese rats. Conclusion: Increase in body weight is associated with the increase in fat deposition in the liver tissues which further develops into inflammation and necrosis of liver cells. Keywords: Wistar rats, Hypercalorie/cafeteria diet, Obese rats, Histopathological examination.